THE INFLUENCE OF AUDITOR QUALITY, LIQUIDITY, PROFITABILITY, AND SOLVENCY ON AUDIT DELAY - Margareta Jane Widyawa; Sylvia Fettry (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
This study examines the effect of auditor quality, liquidity, profitability, and solvency on audit delay in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using 252 firm-year observations and a multiple linear regression approach, this study aims to provide empirical evidence on the determinants of audit timeliness. The study is grounded in agency theory and signaling theory, where auditor quality serves as an external monitoring mechanism to reduce information asymmetry, while profitability acts as a positive signal that encourages timely financial reporting. The empirical results indicate that auditor quality and profitability have a significant negative effect on audit delay, suggesting that companies audited by high-quality auditors and those with stronger financial performance tend to complete the audit process more efficiently. In contrast, liquidity and solvency do not exhibit a significant partial effect on audit delay, indicating that short-term financial capability and leverage are not the primary determinants of audit timeliness. However, the simultaneous test shows that all variables collectively have a significant influence on audit delay. These findings imply that audit delay is primarily driven by audit-related factors and firm performance rather than liquidity or leverage conditions. The results reinforce the relevance of agency theory, particularly the role of high-quality auditors in enhancing audit efficiency. From a practical perspective, this study highlights the importance for companies to engage reputable auditors and maintain strong profitability to ensure timely financial reporting and enhance stakeholder confidence.